2015
DOI: 10.1515/cerce-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties and Fruit Quality of "Jahangiri" (Prunus armeniaca L.) Apricot Fruit under Calcium Chloride Treatment

Abstract: Worldwide, the nutritional value and health benefit of apricot fruit (Prunus armeniaca L., Rosaceae) has been known. The present study was therefore undertaken to assess the effects of CaCl2 pre harvest treatment on some of the biochemical properties and fruit quality of "Jahangiri" (Prunus armeniaca L.) apricot at harvest time and during four weeks cold storage at 0°C. The combined analysis of variances indicated that year had a significant influence on all studied parameters of "Jahangiri" cultivar. CaCl2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Almond was common and popular nut that knew the king of nuts. It was full of nutritive value such as proteins, fats, minerals and vitamins (Yousefi, et al, 2015). Almond is an effective healthy food, for the body and the mind.…”
Section: Introductionmentioning
confidence: 99%
“…Almond was common and popular nut that knew the king of nuts. It was full of nutritive value such as proteins, fats, minerals and vitamins (Yousefi, et al, 2015). Almond is an effective healthy food, for the body and the mind.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Marzouk and Kassem (2011) concluded that, spraying calcium chloride on Thompson seedless grapevines was effective in increased berries firmness and decreased the percentage of unmarketable clusters after storage at ambient temperature for seven days. Moreover, pretreatments of these salts are maintaining the quality characteristics of different fruits such as grapes, apples and mangoes (Yousefi et al, 2015, Nigro et al, 2006and Javed et al, 2015. Applications of calcium salts including calcium bicarbonates, chloride and nitrate are used successfully to replace fungicide in controlling the postharvest decays of grape berries (Romanazzi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%